2002
DOI: 10.1039/b200781a
|View full text |Cite
|
Sign up to set email alerts
|

The second virial coefficient of the dipolar two center Lennard-Jones modelElectronic supplementary information (ESI) available: computer programs and ancillary data. See http://www.rsc.org/suppdata/cp/b2/b200781a/

Abstract: The second virial coefficients of two-center Lennard-Jones molecules which contain an embedded point dipole have been determined via numerical integration. A number of models with different reduced bond lengths and dipole moments have been considered. For each model the second virial coefficient has been calculated for a number of temperatures. It is shown that the presence of the dipole moment significantly raises the Boyle temperature and, for a given temperature, reduces the value of the second virial coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 40 publications
1
16
0
5
Order By: Relevance
“…Furthermore, it should be mentioned that the dipole moment was aligned perpendicular to the molecular axis in the derivation of the JC-term [3] while, in the GV-term, the dipole moment was aligned with the molecular axis [4]. Vega et al [14,15] showed that a dipole moment aligned perpendicular to the molecular axis leads to a more substantial effect on physical properties compared to an axial alignment. Therefore, it is expected that the GV-term will underestimate the influence of polar forces on properties, and hence is the main reason why n p is included in the regression routine as an adjustable pure component parameter.…”
Section: Dipolar Termsmentioning
confidence: 98%
“…Furthermore, it should be mentioned that the dipole moment was aligned perpendicular to the molecular axis in the derivation of the JC-term [3] while, in the GV-term, the dipole moment was aligned with the molecular axis [4]. Vega et al [14,15] showed that a dipole moment aligned perpendicular to the molecular axis leads to a more substantial effect on physical properties compared to an axial alignment. Therefore, it is expected that the GV-term will underestimate the influence of polar forces on properties, and hence is the main reason why n p is included in the regression routine as an adjustable pure component parameter.…”
Section: Dipolar Termsmentioning
confidence: 98%
“…These experimental methods and correlations are useful only for the calculation of second and third virial coefficients. In order to calculate higher order integrals, researchers developed molecular based simulation methods such as hit-and-miss Monte Carlo and numerical integration [21,22]. Simple Monte Carlo technique is utilized by Masters and co-workers [23] to evaluate virial coefficients, up to eighth order of, hard convex bodies, hard-spheres with * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, numerical integration based method is used by Vega and co-workers [21,22,24,25] to calculate second, third and fourth virial coefficients of the two-center Lennard-Jones molecules embedded with point quadrupole and dipole moments.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the virial coefficients is an important issue to determine intermolecular interactions with arbitrary values of temperature and thermodynamic properties of real gases [1][2][3][4][5][6][7][8]. In literature, several experimental and theoretical methods have been proposed to obtain accurate and efficient evaluation of the second virial coefficient with various types of potentials [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%